2011
DOI: 10.1164/rccm.201010-1755oc
|View full text |Cite
|
Sign up to set email alerts
|

Viral-mediated Inhibition of Antioxidant Enzymes Contributes to the Pathogenesis of Severe Respiratory Syncytial Virus Bronchiolitis

Abstract: Rationale : Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infections in children, for which no specific treatment or vaccine is currently available. We have previously shown that RSV induces reactive oxygen species in cultured cells and oxidative injury in the lungs of experimentally infected mice. The mechanism(s) of RSV-induced oxidative stress in vivo is not known. Objectives : To measure changes of lung antioxidant enzymes expression/activity and activation of NF-E2-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(182 citation statements)
references
References 51 publications
12
164
1
5
Order By: Relevance
“…Microarray analysis of gene expression studies from hMPV infected airway epithelial cells demonstrated progressively decreased levels of SOD 3, catalase, GST and peroxiredoxin gene expression and protein levels, with a concomitant increase in SOD 2 [63], similar to what has been observed with RSV. These changes in AOE expression was also observed in a mouse model of hMPV infection [11]. Such an increase in SOD 2 expression and decreased expression of catalase, as well as decreased GSH/GSSG ratio, has also been reported in influenza infection both in vitro and in vivo [64][65][66].…”
Section: Potential Regulatory Mechanism Of Aoe Expression In Rsv Infesupporting
confidence: 64%
See 3 more Smart Citations
“…Microarray analysis of gene expression studies from hMPV infected airway epithelial cells demonstrated progressively decreased levels of SOD 3, catalase, GST and peroxiredoxin gene expression and protein levels, with a concomitant increase in SOD 2 [63], similar to what has been observed with RSV. These changes in AOE expression was also observed in a mouse model of hMPV infection [11]. Such an increase in SOD 2 expression and decreased expression of catalase, as well as decreased GSH/GSSG ratio, has also been reported in influenza infection both in vitro and in vivo [64][65][66].…”
Section: Potential Regulatory Mechanism Of Aoe Expression In Rsv Infesupporting
confidence: 64%
“…As Nrf2 positively regulates its own gene transcription, reduced Nrf2 mRNA levels were observed in airway epithelial cells at late time point of RSV infection [8]. Our recent studies indicate that RSV infection is associated with Nrf2 deacetylation, likely due to RSV-induced upregulation of histone deacetylase was confirmed in vivo, both in a mouse model of RSV infection as well as in children with severe bronchiolitis [11].…”
Section: Potential Regulatory Mechanism Of Aoe Expression In Rsv Infementioning
confidence: 54%
See 2 more Smart Citations
“…Дані проведених на сьогодні досліджень свід-чать, що імунна система дітей з ГРРІ хоча і не має грубих первинних і набутих дефектів, але характе-ризується крайньою напруженістю процесів імун-ного реагування, порушенням міжклітинної ко-операції та недостатністю резервних можливос-тей, що є результатом тривалого й масивного ан-тигенного впливу на організм дитини [9][10][11].…”
Section: вступunclassified